Long‐term outcomes of artificial urinary sphincter in female patients with spina bifida. Issue 1 (16th November 2020) - Gasmi, Anis; Perrouin‐Verbe, Marie‐Aimée; Hascoet, Juliette; Bey, Elsa; Jezequel, Magali; Voiry, Caroline; Perrouin‐Verbe, Brigitte; Gamé, Xavier; Manunta, Andrea; Lenormand, Loic; Capon, Grégoire; Peyronnet, Benoit
Abstract: Aims: To report the long‐term functional outcomes of artificial urinary sphincter (AUS) implantation in female patients with spinal dysraphism and stress urinary incontinence (SUI) related to intrinsic sphincter deficiency (ISD). Methods: The charts of all spina bifida female patients with SUI due to ISD who underwent AUS (AMS 800) implantation between 2005 and 2019 at three academic departments of urology were retrospectively reviewed. Reoperation was defined as either revision or explantation of the AUS device. Reoperation‐free survival of the AUS device was estimated using the Kaplan–Meier method. Continence status as per patients' subjective assessment was categorized as follows: complete continence (no pads), improved continence, unchanged SUI or worsened SUI. Results: Twenty‐three patients were included, 69.6% were self‐catheterizing. The median follow‐up was 14 years. Median time to first reoperation was 10 years. Survival rates without reoperation were 85.9%, 41.8%, 34.6%, and 20.9% at 5, 10, 15, 20 years, respectively. Survival rates without AUS explantation were 90.7%, 66.3%, 55.2%, and 41.4% at 5, 10, 15, 20 years, respectively. None of the patients who underwent device explantation had a new AUS implanted. The only predictive factor of reoperation‐free survival was the type of spinal dysraphism (hazards ratio = 3.60 for closed vs. open dysraphism; p  = .04). At last follow‐up, 17 of the 23 patients were fully continent (73.9%). Conclusion: AUS in female patients with spina bifida may be associated with satisfactory long‐term functional outcomes and a high reoperation rate. The median time to first reoperation was similar to what is reported in the male AUS literature (10 years).